Intellectual property protection for agricultural biotechnology: a survey on the Malaysian Research Institutes’ experiences and legal policy - Ismail, Suzi Fadhilah (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
This article focuses on the current legal protection for agricultural biotechnological inventions in Malaysia. As far as Malaysian IP system is concerned, there are two main regimes which are currently in force: patent law and plant variety protection law. Patent law in Malaysia refers to the Patents Act 1983, supplemented by the Patents Regulations 1986, while plant variety protection law in Malaysia is governed by the Protection of New Plant Varieties Act 2004 (PNPVA), supplemented by the Protection of New Plant Varieties Regulations 2008.The discussion is mainly based on the data which has been collected via semi-structured interviews with a number of selected public sector research institutions. The selected research institutions represent a large component of the views of plant breeders in Malaysia. The interviews sought to collect the data in respect of the extent of use of the IPRS, the level of awareness, appropriateness and effectiveness of the existing legal protection. The response was to some extent an indicative of the views of those involved in the industry and R&D of agricultural biotechnology. Besides, the interviews had been of great assistance to identify those areas where further legislative activity might be needed. The patent regime seems to be preferred by the majority of the RIs for the reason that it offers strong and reliable protection over inventions, while the effectiveness of protection offered under the Protection of New Plant Varieties Act 2004 is yet to manifest despite the fact that it is specifically tailored for breeders of new plant varieties in Malaysia. In short, the overall finding is that the Malaysian biotechnology industry is on track to accelerate commercialization in biotechnology with the full support of the National Biotechnology Policy and BiotechCorp.